2017
DOI: 10.7150/jca.18818
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of CTCF in Breast Cancer Cells Selectively Induces Cancer Cell Death via p53

Abstract: CCCTC-binding factor (CTCF), a ubiquitous 11-zinc finger multifunctional protein, has distinct molecular functions, such as transcriptional activation, repression, and chromatin barrier activity, in a locus-specific manner. Elevated CTCF levels in breast cancer cells are known to contribute to tumorigenesis; however, the underlying mechanism remains elusive. We investigated the effect of CTCF expression on breast cancer cell survival and elucidated its mechanism. CTCF depletion in MCF-7 cells led to a decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…Interestingly, high ratio of CTCF/TP53 was accompanied by a shorter disease free survival time while the prognosis of the high TP53/CTCF ratio group was good ( Supplementary Figure 5C ). A previous study [ 27 ] identified CTCF binding site (CBS) in the promoter region approximately 800 bp upstream of the P53 transcription start site ( Figure 6D ). Therefore, ChIP-qPCR and ChIP-PCR assays were performed to confirm whether CTCF can bind to the site in CRC ( Supplementary Figure 6A and Figure 6F ).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Interestingly, high ratio of CTCF/TP53 was accompanied by a shorter disease free survival time while the prognosis of the high TP53/CTCF ratio group was good ( Supplementary Figure 5C ). A previous study [ 27 ] identified CTCF binding site (CBS) in the promoter region approximately 800 bp upstream of the P53 transcription start site ( Figure 6D ). Therefore, ChIP-qPCR and ChIP-PCR assays were performed to confirm whether CTCF can bind to the site in CRC ( Supplementary Figure 6A and Figure 6F ).…”
Section: Resultsmentioning
confidence: 87%
“…GSEA revealed that CTCF expression is closely related to P53-related gene set signatures. A previous study reported that CTCF transcriptionally inhibits P53 in breast cancer [ 27 ]. Hence, we performed qRT-PCR, ChIP and dual luciferase reporter assays to investigate whether the regulatory mechanism between CTCF and P53 also exists in CRC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the effect of mutations on CTCF binding was found to be non-uniform, for instance different mutations in its zinc finger 3 domain led to selective inhibition of binding to different targets suggesting that there is a tumor-specific change of function rather than loss of function 38 . Furthermore, CTCF was shown to be elevated in breast cancer cell lines and breast tumors 39 , its overexpression was suggested to protect tumor cells from induction of apoptotic cell death 40 while its downregulation in breast cancer cell lines was shown to be associated with reduced cell proliferation 41,42 , both effects via transcriptional regulation of target genes. In line with these results we find overall increased chromatin binding of CTCF in G12V MCF10A cells, although without detectable elevation in its gene expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…CTCF can act as both tumor suppressor and oncogene depending on the type of cancer (229, 230). In ovarian cancer, CTCF expression is upregulated and shows association with poor prognosis (231).…”
Section: Classification Of Mbpsmentioning
confidence: 99%